Faktor Penentu Preferensi Tipe Hunian di Kalangan Mahasiswa - Imega Reski; Angela Christysonia Tampubolon (RUAS (Review of Urbanism and Architectural Studies), 2019)
The universities development in Indonesia has implications on the increasing number of students. The tendency of the students majority who are transmigrants in the relevant college areas has further implications on the increasing need of shelter. Different backgrounds made different needs. Thus, there are several types of dwellings with their own characteristics. This study divides the dwellings into seven types, namely parents’ house, relatives’ house, bought house, apartment, unit rented house, rented house and dormitory. This study attempts to examine dwelling type preference factors. This study also attempts to find the key factors that became the main preference differentiators, and also comparing the respondent's importance level to each key factor on each dwelling type. The data were collected through a two-stage questionnaire. The results of the pilot phase questionnaire were analyzed qualitatively and became the framework of second phase questionnaire. The exploratory research data were then analyzed quantitatively using factor analysis and ANOVA. The results showed that there were 14 dwelling type preference factors with four preference key factors which differed significantly on the importance level valuation of each dwelling type, namely independency, social interaction, freedom, and privacy. The key factors’ importance level diagram on each dwelling types is served.